2020
DOI: 10.3390/plants9101354
|View full text |Cite
|
Sign up to set email alerts
|

Complete Chloroplast Genome of Argania spinosa: Structural Organization and Phylogenetic Relationships in Sapotaceae

Abstract: Argania spinosa (Sapotaceae), an important endemic Moroccan oil tree, is a primary source of argan oil, which has numerous dietary and medicinal proprieties. The plant species occupies the mid-western part of Morocco and provides great environmental and socioeconomic benefits. The complete chloroplast (cp) genome of A. spinosa was sequenced, assembled, and analyzed in comparison with those of two Sapotaceae members. The A. spinosa cp genome is 158,848 bp long, with an average GC content of 36.8%. The cp genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 56 publications
3
13
0
Order By: Relevance
“…The mVISTA results revealed that coding regions were more conserved than the non-coding regions, and the SSC and LSC regions exhibited more variation than IR regions in all cp genomes. The results of this study are consistent with previous nings in other species [29,73,74,91]. In total, we identi ed ve genes present signi cant variations in these cp genomes, such as matK, accD, ycf1, ndhF, and rpl22.…”
Section: Features Of Complete Chloroplast Genome and Comparative Analysessupporting
confidence: 91%
“…The mVISTA results revealed that coding regions were more conserved than the non-coding regions, and the SSC and LSC regions exhibited more variation than IR regions in all cp genomes. The results of this study are consistent with previous nings in other species [29,73,74,91]. In total, we identi ed ve genes present signi cant variations in these cp genomes, such as matK, accD, ycf1, ndhF, and rpl22.…”
Section: Features Of Complete Chloroplast Genome and Comparative Analysessupporting
confidence: 91%
“…The complete plastome of C. sinensis was sequenced, assembled, and analyzed in comparison with these members of subtribe Calypsoinae. The plastome of C. sinensis shows a typical quadripartite structure, as reported for most angiosperms ( Khayi et al., 2020 ; Wu et al., 2020 ; Zhu et al., 2020 ). A total of 109 unique genes were identified in the plastome, which contains 68 protein-coding genes, 30 tRNAs, and four rRNAs.…”
Section: Discussionsupporting
confidence: 65%
“…The distance between psbA and the JLA junction varies from 111 bp to 117 bp. Inverted repeat regions in land plants’ cp genomes vary greatly ( Khayi et al, 2020 ). However, studies show that they are the most conserved regions of the chloroplast genome ( Asaf et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%